CASE-BASED LEARNING AND TEACHING EXPERIENCES ABOUT PEOPLE MANAGEMENT IN CONSTRUCTION BUSINESSES - MOHD LATIF, HAFIZAH (Journal of Surveying, Construction and Property, 2024)
In the modern advanced construction industry, students are required to engage in active learning and critical thinking to deliver defect-free outputs and ensure user satisfaction. Case-based learning is an approach that fosters active learning among students. The aim of this research is to present the educational experiences of students and the teaching advances by the educators involved in case-based learning assignments. 155 students enrolled in the people management course received information on theories and their application at construction sites. Case-based learning and teaching were implemented to fulfil the course objectives, focussing on ongoing projects, site defects and the fraud triangle theory as the scope of the case. Students conducted semi-structured interviews with the site personnel, transcribed the recordings and analysed them by referencing the brief notes provided by the educators. The findings indicate that the students exhibited better performance in the learning environment. Case-based learning enhanced their research skills, communication, collaboration, ethical values, engagement and continuous improvement. The findings also show that the significance of appropriate teaching materials and efficient team teaching in case-based teaching is paramount. These elements are essential for creating an engaging learning environment that supports qualitative educational approaches and thereby improves student learning outcomes.